Estimation of R0 for COVID-19 in India through different mathematical model and their comparison - Dwivedi, Nidhi; Gupta, Sujata; Dwivedi, Archana (International Journal Of Community Medicine And Public Health, 2021)
Background: The cases of novel coronavirus (COVID- 2019)-infected pneumonia started since the 19th of December, 2019, in Wuhan (Central China). A large scale outbreak of the disease resulted in a pandemic. This outbreak of the COVID -19 disease has spread on a wide scale. World health organization (WHO) has identified the ongoing outbreak of corona virus disease (COVID 2019) as pandemic on 11 March 2020. Basic reproduction number (R0)- is one of the most important predictors of epidemic severity. It can help to understand the path of the epidemic and to assess the effectiveness of the various interventions to control the epidemic. The purpose of this study is to estimate R0 by using five methods based on the Indian COVID-19 dataset and compare them. Methods: We obtained data on daily confirmed, recovered and deaths cases from official site of ministry of health and family welfare. We implemented 5 mathematical methods to calculate R0. We estimated the number of active cases till 14th of April. We also compare these methods to find out the best method to predict R0. Results: The estimated R0 for the AR, EG, ML, TD, and gamma-distributed methods were 1.0004, 2.102, 1.895, 1.872 and 1.46 respectively. The computed R0 in the TD method is closer to the actual R0 and have a good fit on data as confirmed with MSE criterion. Conclusions: Awareness of the basic reproduction number of COVID-19 is useful for controlling the spread of disease and for planning. It is therefore necessary to know the best method that has better performance.